2020
DOI: 10.1108/apjml-05-2019-0285
|View full text |Cite
|
Sign up to set email alerts
|

Moral norm is the key

Abstract: PurposeThis research extends the theory of planned behaviour (TPB) and aims to study the underlying factors that influence Chinese consumers' purchase intentions towards green products. The conceptual model encompasses four elements (subjective norms, perceived behaviour control, moral norms and attitude) and one consumer response (purchase intention).Design/methodology/approachThe current research employs a questionnaire survey and two experiments. In Study 1, the hypotheses were tested using structural equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 85 publications
(151 reference statements)
8
128
1
8
Order By: Relevance
“…Numerous studies on tourism marketing have shown how SN positively influences intention and behavior (Liu et al, 2020;Wang & Wong, 2020). Wang and Wong (2020) adopted the TPB model and found that SN positively affected intention in the context of environmentally friendly hotel selection.…”
Section: Subjective Norm (Sn) Toward Intentionmentioning
confidence: 99%
“…Numerous studies on tourism marketing have shown how SN positively influences intention and behavior (Liu et al, 2020;Wang & Wong, 2020). Wang and Wong (2020) adopted the TPB model and found that SN positively affected intention in the context of environmentally friendly hotel selection.…”
Section: Subjective Norm (Sn) Toward Intentionmentioning
confidence: 99%
“…Theory of Reasoned Action has a limited inability to handle individual behavior control. The theory of planned behaviour is the intention of individuals to do something given by the level of practice (Liu et al, 2020).…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Bashir (2019) found brand awareness has a significant positive effect on purchase intention. Aside from both factors, according to Theory of Planned Behavior (TPB) developed by Liu et al (2020), intentions are built from three main components namely attitudes toward behavior, subjective norms, and perceived behavioral control. Everyone needs to realize that behavioral beliefs, normative beliefs, and control beliefs are influenced by various factors such as personal, cultural, and situation factors.…”
mentioning
confidence: 99%
“…TPB had been used in various studies such as explaining behaviours in various settings such teaching environment (Opoku et al, 2020), banking sectors (Kashif et al, 2017), green purchase intention (Liu et al, 2020) and food sector (Thaivalappil et al, 2019). Apart from that, several studies had also underpinned their studies using TPB in the agriculture (Rezaei et al, 2019;Savari & Gharechaee, 2020) including the use of pesticide in farming activities (Bagheri, Bondori, et al, 2019;Khan et al, 2021;Monfared et al, 2015;Wang et al, 2017).…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…The Theory of Planned Behaviour (TPB) and intention have been analyzed in a variety of studies to clarify behaviors in a variety of settings, including the classroom (Opoku et al, 2020), banking (Kashif et al, 2017), green purchasing intention (Liu et al, 2020), online shopping (Yahya et al, 2020), purchase behaviour (Mushi, 2019) and the food sector (Kashif et al, 2017). (Thaivalappil et al, 2019).…”
Section: Introductionmentioning
confidence: 99%